Protecting biodiversity to support ecosystem services: An analysis of trade‐offs and synergies in southwestern China. Issue 9 (12th July 2022) - Lin, Ziyan; Wu, Tong; Xiao, Yi; Rao, Enming; Shi, Xuewei; Ouyang, Zhiyun
Abstract: Biodiversity plays a key role in supporting ecosystem services. Understanding this relationship sheds light on the linkages between ecological structure and functioning, thereby increasing the capacity for effective strategies of ecosystem conservation and restoration. Focusing on southwestern China, a global biodiversity hotspot, we evaluated the spatial correlations between biodiversity and four regulating services and one cultural service. We calculated critical points of change in the relationship between biodiversity and each of these ecosystem services and categorized the region into 'threshold', 'sensitive', 'saturation', 'recession' and 'low‐value' areas. The results show that the spatial correlation between biodiversity and regulating services was mainly positive in the Nujiang River and Lancang River basins and the Dayao Mountains, while biodiversity was negatively correlated with provisioning and cultural services in the Qionglai and Hengduan Mountains. The slope value of the curve fitted for the biodiversity–ecosystem service relationships was approximately 1 when species richness was approximately 50; the corresponding areas were termed threshold areas and were pivotal zones of change in the biodiversity–ecosystem service relationships. These areas were mainly distributed in the Qionglai Mountains, Hengduan Mountains and Nujiang River Basin, and should be prioritized for monitoring and biodiversity protection. Synthesis and applications : Our findings can help improve understanding of the spatially complex interactions between biodiversity and multiple ecosystem services, as well as identifying areas that should be prioritized for protection and restoration; they also contribute towards a scientific framework for integrated management and policy in general. Abstract : Our findings can help improve understanding of the spatially complex interactions between biodiversity and multiple ecosystem services, as well as identifying areas that should be prioritized for protection and restoration; they also contribute towards a scientific framework for integrated management and policy in general.